THE MAIN PROBLEMS IN THE TRANSLATION FIELD AND POTENTIAL SOLUTIONS TO THE PROBLEMS - Bozorova Vasila Ilhom qizi; Kurvonbekov Manuchekhr Islomjon ugli (Web of Journals Publishing, 2024)
This article focuses on the main problems in the field of translation and their appropriate solutions. Also, the opinions of skilled translation scientists on these problems will be discussed.
Keywords: compound words, multiple meanings, cultural diversity, highly technical translations, translation sarcasm, context, translation of verbs.